Inupiaq writing and international Inuit relations - Kaplan, Lawrence (Études/Inuit/Studies, 2005)
AbstractLanguage shift in Alaska threatens to replace Inupiaq, and other indigenous languages, with English unless the conditions that create the shift are reversed. The vitality of West Greenlandic and Inuktitut in the Eastern Arctic can exert a positive influence on the west if Inuit groups share published materials and increase international communication in their own language. Congruent writing systems are crucial to the process of reading what other Inuit write. A comparison of the orthographies used for Alaskan Inupiaq and West Greenlandic shows how differing systems can complicate international written exchange.